ANALISIS KEWAJIBAN PERPAJAKAN PPH 23 ATAS JASA IKLAN - Nugrahini Kusumawati; Efi Tajuroh Afiah; Farina Febiyanti (LPPM Universitas Bina Bangsa, 2023)
Diskominfo Serang City as a government-owned agency in the field of communication and information processing, of course, needs to carry out supervision and continue to inform the public about the latest Covid-19 status through the internet and placing advertisements in collaboration with partners such as press, telecommunications, radio and other media companies. The company partners will be subject to Article 23 Income Tax for advertising services which will be collected, paid, and reported. This research aims to determine the withholding, deposit and reporting of income tax article 23 on advertising services. The research method used is descriptive qualitative where direct observations and interviews are carried out. The results showed that the income tax obligation article 23 in withholding, depositing and reporting at the Diskominfo of Serang City was in accordance with Law No. 36 of 2008 regarding income from other services regulated in PMK No. 141/PMK.03/2015. It can be concluded that Article 23 Income Tax for the use of services by other parties at the Serang City Communication and Information Office is deducted and deposited by the Serang Communication and Information Agency Treasurer at a rate of 2% in accordance with the Regulation of the Minister of Finance Number 244/PMK.03/2008 concerning Other Types of Services